Longitudinal changes in brain connectivity correlate with neuropsychological testing in brain tumor resection patients - Ellis, David G.; Garlinghouse, Matthew; Warren, David E.; Aizenberg, Michele R. (Frontiers in Neuroscience, 2025)
BackgroundPatients undergoing brain tumor resection experience neurological and cognitive (i.e., neurocognitive) changes reflected in altered performance on neuropsychological tests. These changes can be difficult to explain or predict. Brain connectivity, measured with neuroimaging, offers one potential model for examining these changes. In this study, we evaluated whether longitudinal changes in brain connectivity correlated with changes in neurocognitive abilities in patients before and after brain tumor resection.MethodsPatients underwent functional and diffusion MR scanning and neuropsychological evaluation before tumor resection followed by repeat scanning and evaluation 2 weeks post-resection. Using this functional and diffusion imaging data, we measured changes in the topology of the functional and structural networks. From the neuropsychological testing scores, we derived a composite score that described a patient’s overall level of neurocognitive functioning. We then used a multiple linear regression model to test whether structural and functional connectivity measures were correlated with changes in composite scores.ResultsMultiple linear regression on 21 subjects showed that functional connectivity changes were highly correlated with changes in neuropsychological evaluation scores (R2 adjusted = 0.79, p < 0.001). Changes in functional local efficiency (p < 0.001) and global efficiency (p < 0.05) were inversely correlated with changes in composite score, while changes in modularity (p < 0.01) as well as the patient’s age (p < 0.05) were directly correlated with changes in composite score.ConclusionShort interval changes in brain functional connectivity markers were strongly correlated with changes in the composite neuropsychological test scores in brain tumor resection patients. Our findings support the need for further exploration of brain connectivity as a biomarker relevant to brain tumor patients.